Synthesis of a nano-sized hybrid C3N4/TiO2 sample for enhanced and steady solar energy absorption and utilization. Issue 1 (21st January 2017) - Yan, Junqing; Li, Ping; Bian, Hui; Wu, Huan; Liu, Shengzhong (Frank)
Abstract : A sub-15 nm C3 N4 /TiO2 heterojunction is reported for the steady and constant photocatalytic hydrogen evolution under weak and strong incident light conditions. Abstract : The effect of maximum incident light absorption, conversion and utilization by a semiconductor on solar fuel generation was investigated in this study. Sub-15 nm g-C3 N4 –TiO2 (CN–TiO2 ) was synthesized through a hydrothermal process at a relatively high temperature. Three samples with different TiO2 sizes, i.e. 9, 12 and 15 nm, were obtained by changing the pH of solution and named CN–TiO2 -9, CN–TiO2 -12 and CN–TiO2 -15. Based on the Mie scattering law, the nano-sized heterojunction samples can achieve almost 100% incident light absorption without reflection. Characterization results from XRD and FTIR indicate that the samples are composed of protonated g-C3 N4 and anatase TiO2 . Further results from TEM images provide information on the size of the synthesized hybrid samples. It is established that the two components together show sub-15 nm particle size. The nano-sized heterojunction delivered considerable solar-to-hydrogen conversion efficiency with the apparent quantum yield (AQY) of 6.9% under 405 nm visible light irradiation. Moreover, it is interesting to find that the AQY values do not decrease when increasing the incident photon flux. The large absorption cross-section area and the prolonged lifetime of photogenerated carriers of the sub-15 nm CN–TiO2 heterojunction are the origin of the high photon-to-electron conversion.